GANSER SYNDROME AS A PARTICULARITY OF THE COGNITIVE DEFICIT IN SCHIZOPHRENIA - Trifu, Simona; Ion, Daniela Elena; Enache, Iulia Ioana; Trifu, Antonia Ioana (International Journal of Research -GRANTHAALAYAH, 2019)
Introduction: Disorganized schizophrenia is a subtype of schizophrenia which is not recognized in the updated version of DSM. It is found in ICD-10 with the name of hebephrenic schizophrenia. The paper presents a 27-year-old patient with multiple admissions at psychiatry for schizophrenia with an unknown onset, initially considered to be paranoid; the current level of disorganization of the behavioral acts, of the language, of the thinking, having the intensity of hebephrenic schizophrenia. The paper presents a Ganser syndrome in association with alcohol consumption and prohibited substances use. Methods: hospitalization, psychiatric evaluation under antipsychotic treatment with haloperidol and zuclopenthixol, counseling, social assistance. Results: The patient fulfills all the criteria for the classification in hebephrenic schizophrenia, with a reserved prognosis and an involuntary accentuated potential considering the multiple admissions, the early onset, the lack of social and family support, the absence of the obvious triggering factor, the resistance to the treatment, the probable association with the substance use. Considering school dropout and the potential subcultural context, it can be considered the presence of a mild to moderate intellectual disability. Conclusions: In the context of the profound dissociation of the behavior, affect and thinking, the patient associate traits from the Ganser syndrome with his vulnerable personality, which are grafted on the halls created by his absent family support and emotional neglect. The bizarre attitudes and positions along with the Ganser syndrome predict a potential catatonic episode.